PENGARUH ENVIRONMENTAL, SOCIAL AND GOVERNANCE DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN ROA DAN DER SEBAGAI VARIABEL KONTROL (Studi Pada Perusahaan Listing di BEI Periode 2017 - 2021) - Mudzakir, Fahmi Utomo; Pangestuti, Irene Rini Demi (Faculty of Economics and Business Diponegoro University, 2023)
BSTRACT This study aims to examine the effect of Environmental, Social and Governance Disclosure on firm value. The variables used in this study are Environmental, Social and Governance Disclosure as independent variables and company value as measured by Tobin's Q as the dependent variable. In addition, this study uses ROA and DER as control variables. This study uses secondary data with a sample size that has been selected using a purposive sampling method of 80 companies listed on the Indonesia Stock Exchange (IDX) in the period 2017 – 2021. The analytical method used in this study is multiple linear analysis and uses IBM SPSS Statistics 25. The results of this study indicate that ESG Disclosure, Environmental Disclosure, and Social Disclosure have a significant positive effect on firm value as measured by Tobin's Q, while Governance Disclosure has an insignificant positive effect on firm value.